Trace level analyses of selected perfluoroalkyl acids in food: Method development and data generation. (August 2020) - Sadia, Mohammad; Yeung, Leo W.Y.; Fiedler, Heidelore
Abstract: To comprise the future requirements to detect low levels of perfluoroalkyl acids (PFAAs) including branched and linear perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorohexane sulfonic acid (PFHxS) in food items, analytical methods for their determination in five different food matrices (cow milk, butter, chicken meat, beef, and fish) were developed and validated. Analytical method for eggs was only validated for PFOS and PFOA because of interfering substance appeared in some samples. The method applied on foods of animal origin includes alkaline digestion, extraction, and clean-up with solid phase extraction and adsorption on granular carbon where necessary. The method was shown effective to eliminate taurodeoxycholic acid (TDC), a bile acid that is an endogenous interference compound in egg samples causing ionization suppression and false positive result for PFOS when 499 > 80 transition was used for quantification. The validation was performed and resulted in recoveries >70% for all three PFAAs, the limits of quantification (LOQs) in all matrices were 3.1 pg g −1, 3.4 pg g −1, and 4.9 pg g −1 for PFHxS, PFOA, and L-PFOS, respectively. The optimized method was successfully applied to 53 food samples from the Swedish market and from developing countries. PFOS and PFOA were detected in all samples. PFHxS was detected in 76% of the samples. Further method development on separating interfering substance from PFHxS in egg is warranted due to relatively high detection of this compound in other food items. With this method, concentrations in the low pg g −1 range in food samples of animal origin were quantified including the branched PFOS isomers. This method can be applied to enforce potential future limit values for PFOS and PFOA as a consequence of the recent European Food Safety Authority (EFSA) recommendation where the tolerable intakes have been drastically lowered. Further method development is needed for foods of plant origin such as vegetables, flour, nuts, or bread. Graphical abstract: Image 1 Highlights: Method for L- and br-PFOS, PFOA, and PFHxS in fatty foods developed and validated. Method successfully applied to food samples at low pg.g-1 range PFOS and PFOA were found in 100% of food samples from four continents. Interfering bile acid (TDC) successfully eliminated from chromatogram. Sensitivity is sufficient to respond to low LOQs as derived from EFSA 2018 recommendation.